Village Head Leadership in Creating Professional Village Apparatus through Human Resource Management - Awaludin Awaludin; Amirudin Amirudin (Goodwood Publishing, 2026)
Purpose: This study aims to analyze the role of village head leadership in realizing professional village apparatus through the implementation of Human Resource Management (HRM) in village government. Research Methodology: This study adopted a qualitative descriptive approach conducted in a purposively selected village government institution. Data were collected from 30 key informants through in-depth interviews, observations, and documentation and analyzed using qualitative data analysis techniques. Results: The findings indicate that village head leadership plays a strategic role in improving the professionalism of the village apparatus through HRM practices, including task allocation based on competence, capacity development, performance evaluation, and enforcement of work discipline. Leadership characterized by integrity and exemplary behavior strengthens work ethics and accountability among the village apparatus. Conclusions: Effective village head leadership, supported by systematic HRM practices, contributes significantly to the realization of a professional village apparatus and the improvement of village governance quality. Limitations: This study is context-specific and based on a qualitative approach in a single village, which may limit its generalizability. The findings rely on self-reported perceptions, which may involve subjectivity. Contributions: This study contributes to the public sector human resource management literature, particularly in the context of village governance, and provides practical insights for strengthening leadership and HRM practices at the village level.